E-MODULE DEVELOPMENT OF WRITING THE SYAIR PERANG MENTENG VERSE-BASED DRAMA SCRIPT USING FLIP HTML 5 (PENGEMBANGAN E-MODUL MENULIS NASKAH DRAMA BERBASIS SYAIR PERANG MENTENG MENGGUNAKAN FLIP HTML 5) - Arba Ina Putri; Nurahayati Nurhayati; Agus Saripudin; Soni Mirizon; Rozaiman bin Makmun (Jurnal Gramatika, 2022)
This research is motivated by the unavailability of teaching materials for writing drama scripts that satisfy the instructional needs of the Palembang Malay Traditional Theater Course. Therefore, development research was conducted to obtain the teaching materials. The procedure starts from needs analysis, expert validation, small group evaluation, and field test. The data of the study were collected using questionnaires, interviews, assessment sheets, and tests. The study show that: (1) all students and lecturers needed an e-module to write a drama script based on the Menteng War Verse using Flip html 5; (2) the e-module design can be categorized as valid based on the material score of 34 (75.55%), language score of 41 (74.54%), and the graphic score of 32 (71.11%); (3) this e-module teaching material can be categorized as practical on the basis of the score obtained, i.e. 11 (73.33%); (4) The e-module teaching material can be categorized as very effective based on the average score increase (45.89). Thus, the e-module can be used as teaching materials to write a drama script of the Menteng War Verse.